Photosynthetic Responses to Irradiance by the Grey Mangrove, Avicennia marina, Grown under Different Light Regimes - Ball, Marilyn C. (1982)
Photosynthetic responses to irradiance by the grey mangrove, Avicennia marina (Forstk.) Vierh var. australasica (Walp.) Moldenke, were studied using seedlings grown under natural understory shade and exposed conditions as well as in the laboratory under high and low light regimes, i.e. 100% and 6% sunlight, respectively. Leaves in exposed locations were subjected to daylight quantum flux densities greater than 1,000 microeinsteins per square meter per second from 0900 to 1700 hours, whereas those in understory shade experienced only 30 to 120 microeinsteins per square meter per second, interrupted for brief periods by sunflecks ranging in quantum flux density from 800 to 1,500 microeinsteins per square meter per second. The low light regime was similar in light intensity to that of the understory environment, but lacked sunflecks. Leaves from the understory environment showed several properties of `shade' leaves; i.e. they contained more chlorophyll on both a leaf area and fresh weight basis but had a lower specific weight and greater area than exposed leaves, and were enriched in chlorophyll b relative to a. However, there were no significant differences in either the gas exchange or leaf chlorophyll fluorescence characteristics of the two populations, both being typical of `sun' leaves. Leaves grown in the laboratory under low and high light regimes had similar properties. However, light saturated assimilation rates in the leaves from the low light treatment were 20% less and became light saturated at a lower quantum flux density than those of leaves grown under the high light regime. The ecological significance of these results is discussed.